PENERAPAN FUZZY TSUKAMOTO PADA SISTEM IRIGASI SAWAH BERBASIS INTERNET OF THINGS DI KECAMATAN REMBOKEN SULAWESI UTARA - Inda, Inda; Rantung, Vivi P; Santa, Kristofel (Journal of Innovation And Future Technology (IFTECH), 2024)
The Internet of Things is a dynamic and rapidly evolving technology concept in which physical objects and electronic devices are connected to the internet, enabling data exchange and control between devices. In an effort to increase the efficiency of irrigation systems in rice fields, Internet of Things technology can be a very potential solution. IoT enables real-time data collection from various sensors installed in the field, enabling smarter and more timely decisions. However, to optimize management of rice fields, a method is needed that is able to manage sensor data well, and the Tsukamoto fuzzy method is one method that is able to provide this solution. The aim of this research is to increase the efficiency of water use in irrigation systems, reduce costs associated with irrigation systems, to develop a system that can make automatic decisions based on IoT sensors and the Tsukamoto Method. This research was carried out in Remboken sub-district, North Sulawesi on irrigated rice fields. The method used is the Tsukamoto method in controlling and solving existing problems. With a good understanding of the challenges and opportunities, it is possible to create Internet of Things solutions that are useful and safe.